GUIA PROFISSIONAL DIGITAL: MAPAS CONCEITUAIS DAS PROFISSÕES ESCOLHIDAS PELOS ALUNOS DO ENSINO MÉDIO - Sobreira, Lucia (2017)
This report aims to present the experience lived in the project "The School Pedro II in the Professional Decision of Secondary Education Students" aimed to promote professional student choice for the preparation of secondary to higher education, technical or job market with the integration of the areas of knowledge and ICT. Starting questions: How to awaken in students a vocation for academic life? How establish the connection between what students want to be in the future and to choose when isn’t a university course? How to take into account the factors that interfere in making professional student decision to build his own knowledge about your chosen profession? The experiment was performed at the State School of Elementary and Secondary Education D. Pedro II (Belem of Para State/Brazil), based on the view that knowledge must be represented in a format that requires coordination with the different forms of knowledge and the organization and use of technology. The results show that the tasks performed by students for professional choice provided information about themselves and the professional world. The conceptual map has contributed as a mediating tool of the teaching, learning and assessment and favored interest, autonomy and participation.